Multi-element metal nanosheet as well as preparation method and application thereof
By preparing multi-metal nanosheets, combining the specific ratio and morphology of rhodium elements with precious metal elements and copper elements, the problem of difficult control of rhodium-based nanomaterials and low utilization of metal atoms is solved, achieving more efficient catalytic effects and wider application fields.
Patent Information
- Application Number
- CN202411792290.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-06
AI Technical Summary
In the prior art, the morphology of rhodium-based nanomaterials is difficult to control, and the low utilization rate of metal atoms leads to poor catalytic effects and a relatively single application field.
A multi-metal nanosheet is provided, including rhodium elements and other metal elements, such as precious metal elements and copper elements. The ratio and morphology of the elements are adjusted by a specific preparation method to form a multi-metal nanosheet with a thickness of 0.5 to 3 nm.
By adjusting the types and ratio of elements, improve catalytic activity and broaden the application fields, especially in electrochemical and thermochemical reactions, it can show better catalytic effects.
Smart Images

Figure CN119703048A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of nano material preparation, and in particular to a multi-element metal nanosheet, a preparation method and application thereof. Background Art
[0002] Nanomaterials have shown significant advantages and great application potential in the fields of photochemistry and catalysis due to their unique physical and chemical properties. In the field of catalysis, nanomaterials often have one or more characteristics of size effect, surface effect, quantum size effect and macroscopic quantum tunneling effect, which makes them significantly superior to traditional catalysts in catalytic activity and selectivity. Especially in the fields of energy, chemical industry and environment, the application of nanocatalysts has made significant progress. For example, in the oxygen reduction reaction, platinum-based catalysts with nanostructures show better electrochemical performance than traditional platinum particles and have been widely studied.
[0003] The morphology control of nanomaterials has a decisive influence on their physical and chemical properties. Fine control of the morphology of nanomaterials can significantly improve / change the catalytic activity of nanocatalysts, and research in this field has become a research hotspot. At present, researchers have successfully prepared nanomaterials with specific morphologies through synthesis methods such as seed growth method and colloidal synthesis method and template technology. These methods can accurately control the size, shape and surface structure of nanomaterials and finely control their physical and chemical properties. For example, by changing the synthesis conditions, researchers can prepare nanomaterials with different crystal surface exposures, and the optical properties or catalytic activities of these materials may be significantly different. In addition, electrochemical methods are also used in the synthesis of nanocatalysts. By regulating the electrochemical parameters, precise control of the nanocrystal growth process can be achieved.
[0004] For rhodium-based nanomaterials, morphology control is also of great significance to their physical and chemical properties. Through precise control of rhodium-based nanomaterials, materials with diverse uses can be developed to meet the application needs of multiple fields. To this end, it is urgent to propose a new preparation method for multi-metal nanosheets. Summary of the invention
[0005] The main purpose of the present invention is to provide a multi-metal nanosheet, a preparation method and application thereof, so as to solve the problems in the prior art that the morphology of rhodium-based nanomaterials is difficult to control, the utilization rate of metal atoms is low resulting in poor catalytic effect and a relatively single application field.
[0006] In order to achieve the above-mentioned purpose, the present invention provides a multi-metal nanosheet on the one hand, which includes rhodium and other metal elements, the other metal elements are selected from precious metal elements and / or copper elements, and the precious metal elements are selected from one or more of the group consisting of palladium, ruthenium and platinum; the thickness of the multi-metal nanosheet is 0.5~3nm, and the weight ratio of rhodium to other metal elements is (1~65):1.
[0007] Furthermore, the other metal elements are precious metal elements, and the multi-metal nanosheets include rhodium element and alloys formed by rhodium element and precious metal elements; or, the other metal elements are precious metal elements and copper elements, and the multi-metal nanosheets include rhodium element, alloys formed by rhodium element and precious metal elements, and alloys formed by rhodium element and copper elements; or the other metal elements are copper elements, and the multi-metal nanosheets include rhodium element and alloys formed by rhodium element and copper elements.
[0008] Further, the multi-metal nanosheet includes rhodium and palladium, and the weight ratio of rhodium to palladium is (2-50):1; or, the multi-metal nanosheet includes rhodium and platinum, and the weight ratio of rhodium to platinum is (5-20):1; or, the multi-metal nanosheet includes rhodium, palladium and copper, and the ratio of the weight of rhodium to the sum of the weights of palladium and copper is (2-60):1, and the weight ratio of palladium to copper is (3-20):1; or, the multi-metal nanosheet includes rhodium, platinum and copper, and the ratio of the weight of rhodium to the sum of the weights of platinum and copper is (2-65):1, and the weight ratio of platinum to copper is (3-25):1.
[0009] Furthermore, the specific surface area of the multi-metal nanosheets is 820 to 2000 cm 2 / g.
[0010] In order to achieve the above-mentioned purpose, another aspect of the present invention also provides a method for preparing the above-mentioned multi-metal nanosheets provided by the present application, and the preparation method comprises: step S1, mixing a rhodium source, a first metal carbonyl compound and a first organic solvent to obtain a first mixed system; step S2, allowing the first mixed system to undergo a first reaction under heating conditions to obtain a first product system containing rhodium nanosheets, and obtaining rhodium nanosheets after a first solid-liquid separation; step S3, mixing rhodium nanosheets, other metal sources, a second metal carbonyl compound and a second organic solvent to obtain a second mixed system; wherein the other metal sources include precious metal sources and / or copper sources, and the precious metal sources are compounds containing precious metal elements; the weight ratio of the rhodium element in the rhodium nanosheets to the other metal elements in the other metal sources is (1 to 65):1; step S4, allowing the second mixed system to undergo a second reaction under heating conditions to obtain a second product system, and obtaining the multi-metal nanosheets after a second solid-liquid separation and drying treatment.
[0011] Furthermore, in the second mixed system, the mass concentration of rhodium nanosheets is 0.05-0.4 mg / mL.
[0012] Furthermore, in the second mixed system, the molar concentration of other metal sources is 0.01-3 μmol / mL.
[0013] Furthermore, in the first mixed system, the molar concentration of the rhodium source is 0.1 to 5 μmol / mL.
[0014] Furthermore, the molar ratio of the rhodium source to the first carbonyl compound is 1:(1-6).
[0015] Further, the rhodium source is selected from one or more of the group consisting of rhodium chloride, rhodium chloride trihydrate, rhodium bromide, rhodium bromide dihydrate and rhodium acetylacetonate.
[0016] Furthermore, the first metal carbonyl compound is selected from one or more of the group consisting of molybdenum hexacarbonyl, iron pentacarbonyl and tungsten hexacarbonyl.
[0017] Furthermore, the first organic solvent is selected from one or more of the group consisting of oleylamine, octadecene, oleic acid and toluene.
[0018] Furthermore, the temperature of the first reaction is 140-200° C., and the time is 2-8 hours.
[0019] Further, the first reaction is carried out in a protective gas and an optional reducing gas, preferably the protective gas is selected from nitrogen and / or argon, and the reducing gas is carbon monoxide.
[0020] Furthermore, step S2 also includes: after the first reaction is completed, cooling to room temperature at a cooling rate of 10 to 40°C / min, and obtaining rhodium nanosheets after a first solid-liquid separation.
[0021] Furthermore, the first solid-liquid separation is performed by centrifugation, preferably with a centrifugal speed of 1500 to 2500 r / min and a time of 1 to 3 min.
[0022] Furthermore, the molar ratio of the other metal source to the second carbonyl compound is 1:(1-11).
[0023] Further, the precious metal source is selected from one or more of the group consisting of palladium acetylacetonate, palladium chloride, ruthenium acetylacetonate, ruthenium chloride, platinum acetylacetonate and chloroplatinic acid; and / or one or more of the group consisting of hydrates of palladium chloride, ruthenium chloride and chloroplatinic acid.
[0024] Further, the copper source is selected from copper acetylacetonate and / or copper chloride.
[0025] Furthermore, the second metal carbonyl compound is selected from one or more of the group consisting of molybdenum hexacarbonyl, iron pentacarbonyl and tungsten hexacarbonyl.
[0026] Furthermore, the second organic solvent is selected from oleylamine and / or oleic acid.
[0027] Furthermore, the second reaction is carried out in a mixed atmosphere of protective gas and carbon monoxide. Preferably, in the second reaction, the volume ratio of carbon monoxide to protective gas is (0.5-50):1; preferably, the protective gas in the second reaction is selected from nitrogen and / or argon.
[0028] Furthermore, the temperature of the second reaction is 110 to 190° C., preferably 120 to 140° C., and the time is 1 to 6 hours, preferably 2 to 4 hours.
[0029] Furthermore, step S4 also includes: washing to remove impurities after the second solid-liquid separation, and then drying to obtain multi-metal nanosheets.
[0030] Furthermore, a mixed solution of n-hexane and ethanol is used for washing, preferably three times, with washing speeds of 3000-4000 r / min, 2400-3600 r / min and 1800-2800 r / min, respectively, and the time of each washing is independently 1-3 min.
[0031] Furthermore, the second solid-liquid separation is performed by centrifugation, preferably with a centrifugal speed of 2000-4000 r / min and a time of 1-3 min.
[0032] Furthermore, the drying temperature is 70 to 90° C. and the drying time is 12 to 24 hours.
[0033] Furthermore, step S4 also includes: after the second heat treatment is completed, the temperature of the second product system is reduced to 80°C at a cooling rate of 10-40°C / min, a second solid-liquid separation is performed using n-hexane, and multi-metal nanosheets are obtained after drying.
[0034] Another aspect of the present invention provides a method for electrolyzing water, CO 2 Applications in electroreduction reaction, oxygen reduction reaction, formic acid oxidation reaction, methanol oxidation reaction, CO oxidation reaction, NOx oxidation reaction, and hydrogenation catalytic reaction.
[0035] By applying the technical solution of the present invention, compared with the nanosheet containing only rhodium element, the multi-metal nanosheet provided by the present application includes the above-mentioned specific ratio of rhodium element (Rh) and other metal elements, and the other metal elements are selected from precious metal elements (one or more of Pd, Ru and Pt) and / or copper (Cu), and can catalyze different reactions by adjusting the type and ratio of elements, thereby improving the catalytic activity. Compared with other ranges, limiting the thickness of the multi-metal nanosheet to the above range can better exert the catalytic effect of the multi-metal nanosheet, thereby facilitating electrochemical reactions (such as electrolysis of water, electroreduction of CO 2 , oxygen reduction reaction, formic acid oxidation reaction, methanol oxidation reaction) and thermochemical reactions (such as CO oxidation reaction, NOx oxidation reaction, hydrogenation catalytic reaction of organic compounds such as phenol and anthracene), thereby broadening its application fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0037] Figure 1 The transmission electron microscope image (TEM image) of the multi-metal nanosheet prepared in Example 1 of the present application is shown;
[0038] Figure 2 The element distribution diagram of the multi-metal nanosheet prepared in Example 1 of the present application is shown. DETAILED DESCRIPTION
[0039] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.
[0040] As described in the background technology, the existing rhodium-based nanomaterials have the problems of difficult to control morphology, low metal atom utilization rate resulting in poor catalytic effect and relatively single application field. In order to solve the above technical problems, the first aspect of the present application provides a multi-metal nanosheet, which includes rhodium and other metal elements, the other metal elements are selected from precious metal elements and / or copper elements, and the precious metal elements are selected from one or more of the group consisting of palladium, ruthenium and platinum; the thickness of the multi-metal nanosheet is 0.5-3nm, and the weight ratio of rhodium to other metal elements is (1-65):1.
[0041] Compared with nanosheets containing only rhodium, the multi-metal nanosheets provided in the present application include the above-mentioned specific ratio of rhodium (Rh) and other metal elements, and the other metal elements are selected from precious metal elements (one or more of Pd, Ru and Pt) and / or copper (Cu), which can catalyze different reactions by adjusting the type and ratio of elements, thereby improving the catalytic activity. Compared with other ranges, limiting the thickness of the multi-metal nanosheet to the above range can better exert the catalytic effect of the multi-metal nanosheet, thereby facilitating electrochemical reactions (such as electrolysis of water, electroreduction of CO 2 , oxygen reduction reaction, formic acid oxidation reaction, methanol oxidation reaction) and thermochemical reactions (such as CO oxidation reaction, NOx oxidation reaction, hydrogenation catalytic reaction of organic compounds such as phenol and anthracene), thereby broadening its application fields.
[0042] In a preferred embodiment, the other metal elements are noble metal elements, and the multinary metal nanosheets include rhodium and alloys formed by rhodium and noble metal elements; or, the other metal elements are noble metal elements and copper elements, and the multinary metal nanosheets include rhodium, alloys formed by rhodium and noble metal elements, and alloys formed by rhodium and copper elements; or the other metal elements are copper elements, and the multinary metal nanosheets include rhodium and alloys formed by rhodium and copper elements. Compared with metal rhodium nanosheets, the multinary metal nanosheets provided in the present application include the above-mentioned rhodium and alloys formed by rhodium and noble metal elements and / or copper elements, which are conducive to adjusting the adsorption characteristics of different reactants and intermediates on the surface of the multinary metal nanosheets, thereby improving the catalytic activity in a targeted manner and expanding the application range of rhodium-based catalysts.
[0043] In a preferred embodiment, the multi-metal nanosheets include rhodium and palladium, and the weight ratio of rhodium to palladium is (2-50): 1; or, the multi-metal nanosheets include rhodium and platinum, and the weight ratio of rhodium to platinum is (5-20): 1. Compared with other ranges, limiting the above elements and their weight ratios within the above range is conducive to full alloying of Rh and the above other metal elements, which is conducive to improving the utilization rate of metal atoms, thereby improving the catalytic activity, and further broadening its application field.
[0044] In a preferred embodiment, the multi-metal nanosheets include rhodium, palladium and copper, and the weight ratio of the rhodium element to the sum of the weights of the palladium element and the copper element is (2-60):1, and the weight ratio of the palladium element to the copper element is (3-20):1; or, the multi-metal nanosheets include rhodium, platinum and copper, and the weight ratio of the rhodium element to the sum of the weights of the platinum element and the copper element is (2-65):1, and the weight ratio of the platinum element to the copper element is (3-25):1. Compared with other ranges, limiting the above elements and their weight ratios within the above range is conducive to full alloying of Rh and the above other metal elements, and is conducive to improving the utilization rate of metal atoms, thereby helping to improve catalytic activity, and further broadening its application field.
[0045] In order to further improve the catalytic activity and catalytic effect of the multi-metal nanosheets, preferably, the specific surface area of the multi-metal nanosheets is 820 to 2000 cm 2 / g.
[0046] The second aspect of the present application provides a method for preparing the above-mentioned multi-metal nanosheets provided by the present application, and the preparation method comprises: step S1, mixing a rhodium source, a first metal carbonyl compound and a first organic solvent to obtain a first mixed system; step S2, allowing the first mixed system to undergo a first reaction under heating conditions to obtain a first product system containing rhodium nanosheets, and obtaining rhodium nanosheets after a first solid-liquid separation; step S3, mixing rhodium nanosheets, other metal sources, a second metal carbonyl compound and a second organic solvent to obtain a second mixed system; wherein the other metal sources include precious metal sources and / or copper sources, and the precious metal sources are compounds containing precious metal elements; the weight ratio of the rhodium element in the rhodium nanosheets to the other metal elements in the other metal sources is (1 to 65):1; step S4, allowing the second mixed system to undergo a second reaction under heating conditions, and obtaining the multi-metal nanosheets after a second solid-liquid separation and drying treatment.
[0047] The rhodium source, the first metal carbonyl compound and the first organic solvent are mixed and subjected to a first reaction. In this process, the first metal carbonyl compound can act as a surface capping agent to regulate the microscopic morphology of the rhodium nanosheets, so that the rhodium nanosheets with a sheet structure are obtained after the first reaction; the rhodium nanosheets, other metal sources, the second metal carbonyl compound and the second organic solvent are mixed and subjected to a second reaction, so that the other metal sources can react with the surface of the rhodium nanosheets and grow to form an alloy of a noble metal source and / or a copper source and metal rhodium, thereby obtaining a multi-metal nanosheet with a higher catalytic reaction. Moreover, in the second reaction process, the second metal carbonyl compound can act as a surface capping agent to regulate the microscopic morphology of the multi-metal nanosheets, forming a two-dimensional material containing rhodium elements and other metal elements of the above-mentioned specific types of sheet structures. In addition, the first metal carbonyl compound and the second metal carbonyl compound can also play a reducing role, reducing the high-priced noble metal in the noble metal source to a low-priced state, thereby forming an alloy with rhodium.
[0048] Compared with other ranges, limiting the weight ratio of rhodium element in rhodium nanosheets to other metal elements in other metal sources within the above range is conducive to better exerting the catalytic effect of multi-metal nanosheets, thereby facilitating electrochemical reactions (such as electrolysis of water, CO 2 It can catalyze various reactions (such as electroreduction reaction, oxygen reduction reaction, formic acid oxidation reaction, methanol oxidation reaction) and thermochemical reactions (such as CO oxidation reaction, NOx oxidation reaction, hydrogenation catalytic reaction), thereby broadening its application fields.
[0049] In a preferred embodiment, in the second mixed system, the mass concentration of rhodium nanosheets is 0.05-0.4 mg / mL. The mass concentration of rhodium nanosheets includes but is not limited to the above range, and limiting it within the above range is conducive to forming alloys with other metal elements to obtain multi-metal nanosheets.
[0050] In order to improve the dispersibility of other metal sources and further increase the generation rate of multi-metal nanosheets, preferably, in the second mixed system, the molar concentration of other metal sources is 0.01-3 μmol / mL.
[0051] In a preferred embodiment, in the first mixed system, the molar concentration of the rhodium source is 0.1 to 5 μmol / mL. The molar concentration of the rhodium source includes but is not limited to the above range, and limiting it within the above range is beneficial to improving the yield of rhodium nanosheets, and is also beneficial to forming ultrathin rhodium nanosheets, inhibiting the agglomeration of rhodium nanosheets, thereby facilitating the subsequent second reaction.
[0052] In a preferred embodiment, the molar ratio of the rhodium source to the first carbonyl compound is 1:(1-6). The molar ratio of the rhodium source to the first carbonyl compound includes but is not limited to the above range, and limiting it within the above range is beneficial to improving the utilization rate of raw materials and better controlling the formation of sheet-like rhodium nanosheets.
[0053] In order to form sheet-like rhodium nanosheets, preferably, the rhodium source includes, but is not limited to, one or more of the group consisting of rhodium chloride, rhodium chloride trihydrate, rhodium bromide, rhodium bromide dihydrate and rhodium acetylacetonate.
[0054] In order to better play the role of the surface capping agent and better regulate the microscopic morphology of the rhodium nanosheets, preferably, the first metal carbonyl compound includes but is not limited to one or more of the group consisting of molybdenum hexacarbonyl, iron pentacarbonyl and tungsten hexacarbonyl.
[0055] In a preferred embodiment, the first organic solvent includes, but is not limited to, one or more of the group consisting of oleylamine, octadecene, oleic acid and toluene. Compared with other types, the use of the above-mentioned first organic solvent is conducive to improving the dispersibility and compatibility of the rhodium source and the first carbonyl compound, thereby facilitating the improvement of the yield of the rhodium nanosheets.
[0056] In a preferred embodiment, the temperature of the first reaction is 140-200°C and the time is 2-8 hours. The temperature and time of the first reaction include but are not limited to the above ranges, and limiting them within the above ranges is conducive to improving the yield of rhodium nanosheets and facilitating the subsequent second reaction; at the same time, in order to control the thickness of the rhodium nanosheets within an appropriate range, it is convenient to form multi-metal nanosheets of a specific thickness in the subsequent reaction.
[0057] In a preferred embodiment, the first reaction is carried out in a protective gas and an optional reducing gas, preferably the protective gas is selected from nitrogen and / or argon, and the reducing gas is carbon monoxide. The first carbonyl compound can also provide a partial reduction effect. At the same time, in order to make the first reaction process in a reducing atmosphere, carbon monoxide is preferably introduced.
[0058] In a preferred embodiment, step S2 further comprises: after the first reaction is completed, cooling the temperature to room temperature at a cooling rate of 10 to 40°C / min, and performing a first solid-liquid separation to obtain rhodium nanosheets. The above-mentioned cooling process is used to bring the first product system to room temperature, and then the first solid-liquid separation is performed to improve the yield and purity of the rhodium nanosheets.
[0059] In the present application, a commonly used solid-liquid separation method can be used. In a preferred embodiment, the first solid-liquid separation is performed by centrifugation, preferably at a centrifugal speed of 1500 to 2500 r / min and a time of 1 to 3 min. Compared with other ranges, limiting the centrifugal speed and time within the above range is conducive to improving the separation efficiency of rhodium nanosheets, thereby improving its yield.
[0060] In a preferred embodiment, the molar ratio of the other metal source to the second carbonyl compound is 1:(1-11). The molar ratio of the other metal source to the second carbonyl compound includes but is not limited to the above range, and limiting it within the above range is beneficial to improving the utilization rate of raw materials, promoting the formation of alloy phases, and suppressing the generation of impurity phases, thereby facilitating the generation rate and purity of multi-element nanometal sheets.
[0061] In a preferred embodiment, the noble metal source includes, but is not limited to, one or more of the group consisting of palladium acetylacetonate, palladium chloride, ruthenium acetylacetonate, ruthenium chloride, platinum acetylacetonate and chloroplatinic acid; and / or, one or more of the group consisting of hydrates of palladium chloride, ruthenium chloride and chloroplatinic acid. Compared with other types, the use of the above types of noble metal sources is conducive to improving its dispersibility in the second organic solvent, thereby facilitating the second reaction.
[0062] In a preferred embodiment, the copper source includes but is not limited to copper acetylacetonate and / or copper chloride. Compared with other types, the use of the above types of noble metal sources is conducive to improving its dispersibility in the second organic solvent, thereby facilitating the second reaction.
[0063] In a preferred embodiment, the second metal carbonyl compound includes but is not limited to one or more of the group consisting of molybdenum hexacarbonyl, iron pentacarbonyl and tungsten hexacarbonyl. Compared with other types, the use of the second metal carbonyl compound of the above type is conducive to better play the role of the surface capping agent and better control the microscopic morphology of the rhodium nanosheets.
[0064] In order to improve the dispersibility and compatibility of the noble metal source and the second metal carbonyl compound, preferably, the second organic solvent includes but is not limited to oleylamine and / or oleic acid.
[0065] In a preferred embodiment, the second reaction is carried out in a mixed atmosphere of protective gas and carbon monoxide, and the protective gas in the second reaction is preferably selected from nitrogen and / or argon. Carrying out the second reaction in the above-mentioned mixed atmosphere is beneficial to provide a reducing atmosphere for the reaction system, thereby facilitating the alloying growth of other metal sources and rhodium nanosheets, inhibiting the formation of nanostructures such as particles, thereby improving the generation rate and purity of multi-metal nanosheets with sheet structures.
[0066] In order to further effectively control the two-dimensional morphology of the multi-metal nanosheets, preferably, in the second reaction, the volume ratio of carbon monoxide to the protective gas is (0.5-50):1.
[0067] In a preferred embodiment, the temperature of the second reaction is 110-190° C., and the time is 1-6 hours. The temperature and time of the second reaction include but are not limited to the above ranges, and limiting them within the above ranges is conducive to improving the efficiency of the second reaction, thereby facilitating the improvement of the yield of multinary metal nanosheets, and also facilitating the formation of multinary metal nanosheets with uniform thickness.
[0068] In order to further improve the efficiency of the second reaction and increase the yield and thickness uniformity of the multi-metal nanosheets, preferably, the temperature of the second reaction is 120-140° C. and the time is 2-4 hours.
[0069] In a preferred embodiment, step S4 further comprises: washing to remove impurities after the second solid-liquid separation, and then drying to obtain multi-element metal nanosheets. The washing treatment is conducive to removing other impurities, and the drying treatment is conducive to removing the solvent, thereby obtaining multi-element metal nanosheets with higher purity.
[0070] In order to improve the impurity removal rate and thus improve the purity of the multi-metal nanosheets, preferably, a mixed solution of n-hexane and ethanol is used for washing.
[0071] In order to improve the impurity removal rate and thus improve the purity of the multi-metal nanosheets, preferably, the washing times are 3 times, the washing speeds are 3000-4000r / min, 2400-3600r / min and 1800-2800r / min respectively, and the washing time for each washing is independently 1-3min.
[0072] The second solid-liquid separation in the present application can be carried out by a centrifugation method commonly used in the art. In a preferred embodiment, the second solid-liquid separation is carried out by centrifugation, preferably at a centrifugal speed of 2000 to 4000 r / min and a time of 1 to 3 min. Compared with other ranges, limiting the centrifugal speed and time within the above range is conducive to improving the separation efficiency of multi-metal nanosheets, thereby helping to improve their yield and purity.
[0073] In a preferred embodiment, the drying temperature is 70-90°C and the drying time is 12-24 hours. The drying temperature and time include but are not limited to the above ranges, which are conducive to improving the removal rate of residual solvents, thereby reducing the amount of solvent in the multi-metal nanosheets.
[0074] In a preferred embodiment, step S4 further comprises: after the second heat treatment is completed, the temperature of the second product system is reduced to 80°C at a cooling rate of 10-40°C / min, and n-hexane is used for second solid-liquid separation, and multinary metal nanosheets are obtained after drying. Compared with performing the second solid-liquid separation at room temperature, performing the second solid-liquid separation on the second product system while hot is conducive to improving the separation efficiency of the multinary metal nanosheets, thereby improving its yield and purity.
[0075] The third aspect of the present application also provides a method for electrolyzing water, CO 2 The multi-metal nanosheets provided in this application have wide applications in electrochemical reactions and thermochemical reactions, especially in water electrolysis, CO 2 The catalytic activity of the multi-metal nanosheets can be exerted in electroreduction reaction, oxygen reduction reaction, formic acid oxidation reaction, methanol oxidation reaction, CO oxidation reaction, NOx oxidation reaction, and hydrogenation catalytic reaction to improve the catalytic efficiency and thus the reaction efficiency.
[0076] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0077] (I) Preparation Example
[0078] Example 1
[0079] (1) 8.2 mg, 39.2 μmol of rhodium chloride was added to 10 mL of oleylamine, and ultrasonic dispersion was performed until the rhodium chloride was completely dissolved to form a golden solution. Then, 55 mg, 208.33 μmol of molybdenum hexacarbonyl was added under magnetic stirring, and ultrasonic dispersion was performed (temperature was controlled below 10° C.) until a uniform solution was formed, i.e., a first mixed system; then, argon gas was passed into the reaction container for 10 min, the reaction container was sealed, and the reaction was transferred to an oil bath at 160° C. for a first reaction, and the reaction was performed for 5 h. Then, the temperature was lowered to 25° C. at a rate of 25° C. / min, and the mixture was centrifuged at 2000 r / min for 2 min to obtain rhodium nanosheets;
[0080] (2) 3.6 mg of rhodium nanosheets prepared in step (1) were added to 10 mL of oleylamine / oleic acid mixed solvent (the volume ratio of oleylamine to oleic acid was 19:1), and low-temperature ultrasonic dispersion (≤10°C) was used to form a black solution. Then, 3.1 mg and 10.17 μmol of palladium acetylacetonate were added under magnetic stirring. After using a shaking table, 28 mg and 106.06 μmol of molybdenum hexacarbonyl were added, and ultrasonic dispersion was performed to form a uniform solution, i.e., the second mixed system; subsequently, argon gas was passed into the reaction container for 10 min, carbon monoxide (CO) gas (5 sccm) was passed into the reaction container for 5 min, the reaction container was sealed, and transferred to an oil bath at 125°C for the second reaction. After reacting for 3 h, the temperature was lowered to 80°C, 10 mL of n-hexane was added and centrifuged, the solid phase product was washed 3 times with a n-hexane / ethanol mixed solution, and dried in a vacuum oven at 80°C for 18 h to obtain rhodium palladium (Rh-Pd) metal nanosheets.
[0081] like Figure 1 As shown in FIG. 1 , the Rhodium-Pd metal nanosheets have a sheet-like microstructure and a thickness of 1.1 nm. Figure 2 As shown, the Rh element and the Pd element are uniformly dispersed in the rhodium-palladium metal nanosheets prepared in Example 1, which indicates that a Rh-Pd alloy is formed, and the weight ratio of the Rh element to the Pd element is 5:1.
[0082] Example 2
[0083] (1) 12.3 mg, 58.8 μmol of rhodium chloride was added to 15 mL of oleylamine, and ultrasonic dispersion was performed until the rhodium chloride was completely dissolved to form a golden solution. Then, 84 mg, 318.18 μmol of molybdenum hexacarbonyl was added under magnetic stirring, and ultrasonic dispersion was performed (the temperature was controlled below 10° C.) until a uniform solution was formed, i.e., a first mixed system; then, argon gas was passed into the reaction container for 10 min, the reaction container was sealed, and the reaction was transferred to an oil bath at 160° C. for a first reaction, and the reaction was performed for 5 h. Then, the temperature was lowered to 25° C. at a rate of 25° C. / min, and the mixture was centrifuged at 2000 r / min for 2 min to obtain rhodium nanosheets;
[0084] (2) 6 mg of rhodium nanosheets prepared in step (1) were added to 15 mL of oleylamine / oleic acid mixed solvent (the volume ratio of oleylamine to oleic acid was 19:1), and low-temperature ultrasonic dispersion (≤10°C) was used to form a black solution. Then, 3.1 mg, 10.17 μmol of acetylacetonate palladium and 1.9 mg, 4.83 μmol of acetylacetonate platinum were added under magnetic stirring. After using a shaking table, 42 mg, 159.09 μmol of molybdenum hexacarbonyl were added, and ultrasonic dispersion was performed to form a uniform solution. , i.e. the second mixed system; subsequently, argon gas was passed into the reaction container for 10 min, carbon monoxide (CO) gas (5 sccm) was passed into the reaction container for 5 min, the reaction container was sealed, and transferred to an oil bath at 130°C for the second reaction. After reacting for 3 h, the temperature was lowered to 80°C, 10 mL of n-hexane was added and centrifuged, the solid phase product was washed 3 times with a n-hexane / ethanol mixed solution, and dried in a vacuum oven at 80°C for 18 h to obtain rhodium palladium platinum (Rh-Pd-Pt) metal nanosheets.
[0085] Example 3
[0086] The difference from Example 1 is that in the second mixed system, the mass concentration of rhodium nanosheets is 0.05 mg / mL, and the molar concentration of palladium acetylacetonate is 0.01 μmol / mL.
[0087] Example 4
[0088] The difference from Example 1 is that in the second mixed system, the mass concentration of rhodium nanosheets is 0.4 mg / mL, and the molar concentration of palladium acetylacetonate is 3 μmol / mL.
[0089] Example 5
[0090] The difference from Example 1 is that the amount of rhodium chloride added is changed so that the molar concentration of rhodium chloride in the first mixed system is 0.1 μmol / mL.
[0091] Example 6
[0092] The difference from Example 1 is that the amount of rhodium chloride added is changed so that the molar concentration of rhodium chloride in the first mixed system is 5 μmol / mL.
[0093] Example 7
[0094] The difference from Example 1 is that the amount of rhodium chloride added is changed so that the molar concentration of rhodium chloride in the first mixed system is 8 μmol / mL.
[0095] Example 8
[0096] The difference from Example 1 is that in the second mixed system, the amount of molybdenum hexacarbonyl added is 10.3 mg, and the molar ratio of palladium acetylacetonate to molybdenum hexacarbonyl is 1:1.
[0097] Example 9
[0098] The difference from Example 1 is that in the second mixed system, the amount of molybdenum hexacarbonyl added is 103.5 mg, and the molar ratio of palladium acetylacetonate to molybdenum hexacarbonyl is 1:10.
[0099] Example 10
[0100] The difference from Example 1 is that in the second mixed system, the amount of molybdenum hexacarbonyl added is 5.2 mg, and the molar ratio of palladium acetylacetonate to molybdenum hexacarbonyl is 1:0.5.
[0101] Embodiment 11
[0102] The difference from Example 1 is that the temperature of the first reaction is 140° C. and the time is 8 hours.
[0103] Example 12
[0104] The difference from Example 1 is that the temperature of the first reaction is 200° C. and the time is 2 h.
[0105] Example 13
[0106] The difference from Example 1 is that the temperature of the first reaction is 130° C. and the time is 1.5 h.
[0107] Embodiment 14
[0108] The difference from Example 1 is that in the first mixed system, the amount of molybdenum hexacarbonyl added is 2.7 mg, and the molar ratio of rhodium chloride to molybdenum hexacarbonyl is 1:1.
[0109] Embodiment 15
[0110] The difference from Example 1 is that in the first mixed system, the amount of molybdenum hexacarbonyl added is 27.0 mg, and the molar ratio of rhodium chloride to molybdenum hexacarbonyl is 1:10.
[0111] Example 16
[0112] The difference from Example 1 is that in the first mixed system, the amount of molybdenum hexacarbonyl added is 1.4 mg, and the molar ratio of rhodium chloride to molybdenum hexacarbonyl is 1:0.5.
[0113] Embodiment 17
[0114] The difference from Example 1 is that the temperature of the second reaction is 110° C. and the time is 6 hours.
[0115] Embodiment 18
[0116] The difference from Example 1 is that the temperature of the second reaction is 190° C. and the time is 1 hour.
[0117] Embodiment 19
[0118] The difference from Example 1 is that the temperature of the second reaction is 120° C. and the time is 4 hours.
[0119] Embodiment 20
[0120] The difference from Example 1 is that the temperature of the second reaction is 140° C. and the time is 2 h.
[0121] Embodiment 21
[0122] The difference from Example 1 is that the temperature of the second reaction is 200° C. and the time is 0.5 h.
[0123] Embodiment 22
[0124] The difference from Example 1 is that 1.7 mg of copper chloride is also added in step (2) to obtain rhodium-palladium-copper (Rh-Pd-Cu) metal nanosheets.
[0125] Embodiment 23
[0126] The difference from Example 1 is that 1.7 mg of copper chloride is used to replace 3.1 mg of palladium acetylacetonate in step (2) to obtain rhodium-copper (Rh-Cu) metal nanosheets.
[0127] Comparative Example 1
[0128] The difference from Example 1 is that in the second mixed system, the mass concentration of rhodium nanosheets is 0.02 mg / mL, and the molar concentration of palladium acetylacetonate is 5 μmol / mL.
[0129] Comparative Example 2
[0130] The difference from Example 2 is that in the second mixed system, the mass concentration of rhodium nanosheets is 2 mg / mL, and the molar concentration of palladium acetylacetonate is 0.005 μmol / mL.
[0131] Comparative Example 3
[0132] The difference from Example 1 is that: 8.2 mg of rhodium chloride, 83 mg of molybdenum hexacarbonyl, and 3.1 mg of palladium acetylacetonate are dispersed in 20 mL of a mixed solvent of oleylamine and oleic acid to form a precursor solution; a one-step reaction is carried out in an oil bath at 125° C., and after the reaction is completed, the temperature is lowered to 80° C., 10 mL of n-hexane is added and centrifuged, the solid phase product is washed 3 times with a n-hexane / ethanol mixed solution, and dried in a vacuum oven at 80° C. for 18 h to obtain rhodium palladium (Rh-Pd) metal nanosheets.
[0133] Comparative Example 4
[0134] The difference from Example 22 is that in the second mixed system, the mass concentration of rhodium nanosheets is 0.04 mg / mL, and the molar concentration of copper chloride is 7 μmol / mL.
[0135] Comparative Example 5
[0136] The difference from Example 23 is that in the second mixed system, the mass concentration of rhodium nanosheets is 1 mg / mL, and the molar concentration of copper chloride is 0.004 μmol / mL.
[0137] The test results of thickness and specific surface area of multi-element metal nanosheets prepared in all the above embodiments and comparative examples of the present application are shown in Table 1. The thickness is measured by atomic force microscopy (AFM), and the specific surface area is measured by nitrogen isothermal adsorption-desorption curve method.
[0138] Table 1
[0139]
[0140] (II) Application Examples
[0141] (1)CO 2 Electroreduction reaction
[0142] Application Examples 1, 3 to 21
[0143] A three-electrode system was used for CO 2 Electroreduction, wherein 1 mol / L KOH is used as an electrolyte, Hg / HgO is used as a reference electrode, a platinum wire is used as a counter electrode, the diaphragm comprises an anode catalyst layer, an anion exchange membrane layer and a cathode catalyst layer which are stacked in sequence, the rhodium palladium (Rh-Pd) metal nanosheets prepared in Preparation Examples 1, 3 to 21 are respectively used as the material of the cathode catalyst layer, the material of the anode catalyst layer is platinum wire, the thickness of the AEM membrane layer is 60 μm, and the thickness of the cathode catalyst layer is 500 nm.
[0144] Application Example 22
[0145] The difference from Application Example 1 is that the rhodium palladium copper (Rh—Pd—Cu) metal nanosheets prepared in Preparation Example 22 are used as the material for the cathode catalyst layer.
[0146] Application Example 23
[0147] The difference from Application Example 1 is that the rhodium-copper (Rh—Cu) metal nanosheets prepared in Preparation Example 22 are used as the material for the cathode catalyst layer.
[0148] Application Comparative Example 1
[0149] The difference from Application Example 1 is that the rhodium-palladium (Rh—Pd) metal nanosheets prepared in Preparation Comparative Example 1 are used as the material for the cathode catalyst layer.
[0150] Application Comparative Example 3
[0151] The difference from Application Example 1 is that the rhodium-palladium (Rh—Pd) metal nanosheets prepared in Preparation Comparative Example 3 are used as the material for the cathode catalyst layer.
[0152] Application Comparative Example 4
[0153] The difference from Application Example 1 is that the rhodium-palladium-copper (Rh—Pd—Cu) metal nanosheets prepared in Preparation Comparative Example 4 are used as the material for the cathode catalyst layer.
[0154] Application Comparative Example 5
[0155] The difference from Application Example 1 is that the rhodium-copper (Rh—Cu) metal nanosheets prepared in Preparation Comparative Example 5 are used as the material for the cathode catalyst layer.
[0156] The test results are shown in Table 2.
[0157] Table 2
[0158]
[0159]
[0160] (2) Oxygen reduction reaction
[0161] Application Example 2
[0162] A three-electrode system was used for the oxygen reduction reaction, in which 1 mol / L HClO was saturated with oxygen. 4 As electrolyte, platinum wire was used as counter electrode, saturated calomel electrode (SCE) was used as reference electrode, and the test was carried out in a five-necked flask. The rotating disk electrode with the surface loaded with rhodium palladium platinum (Rh-Pd-Pt) metal nanosheets prepared in Preparation Example 2 of the present application was used as working electrode, platinum wire was used as counter electrode, and the loading amount of the working electrode was 1 mg / cm 2 .
[0163] Application Comparative Example 2
[0164] The difference from Application Example 2 is that the rhodium-palladium-platinum (Rh—Pd—Pt) metal nanosheets prepared in Preparation Comparative Example 2 are used as the material for the cathode catalyst layer.
[0165] The test results are shown in Table 3.
[0166] Table 3
[0167] Half-wave potential (V) Application Example 2 0.87V Application Comparative Example 2 0.82V
[0168] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:
[0169] A rhodium source, a first metal carbonyl compound and a first organic solvent are mixed and subjected to a first reaction. In this process, the first metal carbonyl compound can act as a surface capping agent to regulate the microscopic morphology of the rhodium nanosheets, so that rhodium nanosheets with a sheet-like structure are obtained after the first reaction. The rhodium nanosheets, other metal sources, a second metal carbonyl compound and a second organic solvent are mixed and subjected to a second reaction, so that the other metal sources can react with the surface of the rhodium nanosheets and grow to form an alloy of a noble metal source and / or a copper source and metallic rhodium, thereby obtaining multi-metal nanosheets with a higher catalytic reaction. Moreover, in the second reaction process, the second metal carbonyl compound can act as a surface capping agent to regulate the microscopic morphology of the multi-metal nanosheets, forming a two-dimensional material containing rhodium elements and other metal elements of the above-mentioned specific types with a sheet-like structure. In addition, the first metal carbonyl compound and the second metal carbonyl compound can also play a reducing role, reducing the high-valent noble metal in the noble metal source to a low-valent state, thereby forming an alloy with rhodium.
[0170] Compared with nanosheets containing only rhodium, the multi-metal nanosheets provided in the present application include the above-mentioned specific ratio of rhodium (Rh) and other metal elements, and the other metal elements are selected from precious metal elements (one or more of Pd, Ru and Pt) and / or copper elements, and can catalyze different reactions by adjusting the type and ratio of elements, thereby improving the catalytic activity. Compared with other ranges, limiting the thickness of the multi-metal nanosheet to the above range can better exert the catalytic effect of the multi-metal nanosheet, thereby facilitating electrochemical reactions (such as electrolysis of water, electroreduction of CO 2 , oxygen reduction reaction, formic acid oxidation reaction, methanol oxidation reaction) and thermochemical reactions (such as CO oxidation reaction, NOx oxidation reaction, hydrogenation catalytic reaction of organic compounds such as phenol and anthracene), thereby broadening its application fields.
[0171] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein, for example.
[0172] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A multi-metal nanosheet, characterized in that: The multi-metal nanosheet includes rhodium and other metal elements, the other metal elements are selected from precious metal elements and / or copper elements, and the precious metal elements are selected from one or more of the group consisting of palladium, ruthenium and platinum; the thickness of the multi-metal nanosheet is 0.5 to 3 nm, and the weight ratio of the rhodium element to the other metal elements is (1 to 65):
1.
2. The multi-metal nanosheet according to claim 1, characterized in that: The other metal element is a noble metal element, and the multi-metal nanosheet includes a single substance of rhodium and an alloy formed by the rhodium element and the noble metal element; or, the other metal element is a noble metal element and a copper element, and the multi-metal nanosheet includes a single substance of rhodium, an alloy formed by the rhodium element and the noble metal element, and an alloy formed by the rhodium element and the copper element; or the other metal element is a copper element, and the multi-metal nanosheet includes a single substance of rhodium and an alloy formed by the rhodium element and the copper element; Preferably, the multi-metal nanosheet comprises rhodium and palladium, and the weight ratio of the rhodium to the palladium is (2-50):1; or, the multi-metal nanosheet comprises rhodium and platinum, and the weight ratio of the rhodium to the platinum is (5-20):1; or, the multi-metal nanosheet comprises rhodium, palladium and copper, and the ratio of the weight of the rhodium to the sum of the weights of the palladium and the copper is (2-60):1, and the weight ratio of the palladium to the copper is (3-20):1; or, the multi-metal nanosheet comprises rhodium, platinum and copper, and the ratio of the weight of the rhodium to the sum of the weights of the platinum and the copper is (2-65):1, and the weight ratio of the platinum to the copper is (3-25):1; Preferably, the specific surface area of the multi-metal nanosheets is 820 to 2000 cm 2 / g.
3. A method for preparing multi-metal nanosheets according to claim 1 or 2, characterized in that: The preparation method comprises: Step S1, mixing a rhodium source, a first metal carbonyl compound and a first organic solvent to obtain a first mixed system; Step S2, subjecting the first mixed system to a first reaction under heating conditions to obtain a first product system containing rhodium nanosheets, and obtaining the rhodium nanosheets after a first solid-liquid separation; Step S3, mixing the rhodium nanosheets, other metal sources, a second metal carbonyl compound and a second organic solvent to obtain a second mixed system; wherein the other metal source includes a noble metal source and / or a copper source, and the noble metal source is a compound containing a noble metal element; and the weight ratio of the rhodium element in the rhodium nanosheets to the other metal elements in the other metal source is (1-65):1; Step S4, subjecting the second mixed system to a second reaction under heating conditions to obtain a second product system, and obtaining the multi-metal nanosheets after a second solid-liquid separation and drying treatment.
4. The method for preparing multi-element metal nanosheets according to claim 3, characterized in that: In the second mixed system, the mass concentration of the rhodium nanosheets is 0.05-0.4 mg / mL; Preferably, in the second mixed system, the molar concentration of the other metal source is 0.01 to 3 μmol / mL; Preferably, in the first mixed system, the molar concentration of the rhodium source is 0.1 to 5 μmol / mL; Preferably, the molar ratio of the rhodium source to the first carbonyl compound is 1:(1-6); Preferably, the rhodium source is selected from one or more of the group consisting of rhodium chloride, rhodium chloride trihydrate, rhodium bromide, rhodium bromide dihydrate and rhodium acetylacetonate; Preferably, the first metal carbonyl compound is selected from one or more of the group consisting of molybdenum hexacarbonyl, iron pentacarbonyl and tungsten hexacarbonyl; Preferably, the first organic solvent is selected from one or more of the group consisting of oleylamine, octadecene, oleic acid and toluene.
5. The method for preparing multi-element metal nanosheets according to claim 3 or 4, characterized in that: The temperature of the first reaction is 140-200°C and the time is 2-8h; Preferably, the first reaction is carried out in a protective gas and an optional reducing gas, preferably the protective gas is selected from nitrogen and / or argon, and the reducing gas is carbon monoxide; Preferably, the step S2 further comprises: after the first reaction is completed, cooling the temperature to room temperature at a cooling rate of 10 to 40° C. / min, and obtaining the rhodium nanosheets after the first solid-liquid separation; Preferably, the first solid-liquid separation is performed by centrifugation, preferably at a centrifugal speed of 1500 to 2500 r / min and a time of 1 to 3 min.
6. The method for preparing multi-element metal nanosheets according to any one of claims 3 to 5, characterized in that: The molar ratio of the other metal source to the second carbonyl compound is 1:(1-11); Preferably, the noble metal source is selected from one or more of the group consisting of palladium acetylacetonate, palladium chloride, ruthenium acetylacetonate, ruthenium chloride, platinum acetylacetonate and chloroplatinic acid; and / or one or more of the group consisting of hydrates of palladium chloride, ruthenium chloride and chloroplatinic acid; Preferably, the copper source is selected from copper acetylacetonate and / or copper chloride; Preferably, the second metal carbonyl compound is selected from one or more of the group consisting of molybdenum hexacarbonyl, iron pentacarbonyl and tungsten hexacarbonyl; Preferably, the second organic solvent is selected from oleylamine and / or oleic acid.
7. The method for preparing multi-element metal nanosheets according to claim 6, characterized in that: The second reaction is carried out in a mixed atmosphere of a protective gas and carbon monoxide. Preferably, in the second reaction, the volume ratio of the carbon monoxide to the protective gas is (0.5-50):1; preferably, the protective gas in the second reaction is selected from nitrogen and / or argon; Preferably, the temperature of the second reaction is 110-190° C., preferably 120-140° C., and the time is 1-6 h, preferably 2-4 h.
8. The method for preparing multi-element metal nanosheets according to claim 7, characterized in that: The step S4 further comprises: washing to remove impurities after the second solid-liquid separation, and then performing the drying process to obtain the multi-metal nanosheets; Preferably, the washing is performed with a mixture of n-hexane and ethanol, preferably the washing is performed 3 times, the washing speeds are 3000-4000 r / min, 2400-3600 r / min and 1800-2800 r / min, respectively, and the washing time for each washing is independently 1-3 min; Preferably, the second solid-liquid separation is performed by centrifugation, preferably at a centrifugal speed of 2000-4000 r / min and a time of 1-3 min; Preferably, the drying process is carried out at a temperature of 70 to 90° C. and for a time of 12 to 24 hours.
9. The method for preparing multi-element metal nanosheets according to claim 7, characterized in that: The step S4 also includes: after the second heat treatment is completed, reducing the temperature of the second product system to 80° C. at a cooling rate of 10-40° C. / min, performing the second solid-liquid separation with n-hexane, and obtaining the multi-metal nanosheets after the drying treatment.
10. Use of the multi-metal nanosheets according to claim 1 or 2 in water electrolysis, CO2 electroreduction reaction, oxygen reduction reaction, formic acid oxidation reaction, methanol oxidation reaction, CO oxidation reaction, NOx oxidation reaction, and hydrogenation catalytic reaction.
Citation Information
Patent Citations
Metal nanoplate, method for manufacturing same, and conductive ink composition and conductive film comprising metal nanoplate
CN105451917A
Preparation method for multi-metal-core-shell nanosheet
CN106694900A
Rh ultrathin two-dimensional nanosheet and preparation method thereof
CN108273498A
Pt / Rh nano composite material and preparation method and application thereof
CN109078634A
Preparation method and application of ultra-thin multi-metal nanosheet piling assembly material
CN109603800A